Economic crisis in Asia: a future of diminishing growth and increasing poverty? - Rosegrant, Mark W.; Ringler, Claudia (International Food Policy Research Institute, 1998)
After more than a decade of rapid economic growth, many East and Southeast Asian countries face the prospect of a long economic slump, and the poor in these countries face a reversal of their halting climb out of poverty. Recovery from the crisis will depend, in part, on increases in Asia’s exports to some of the larger developed markets, like the United States and Western Europe. But developed countries themselves are suffering from the crisis to varying degrees, depending on their trade and financial links with Asia and pre-crisis economic and financial positions. Long-term scenarios for food supply, demand, and trade indicate that world cereal and livestock prices will decline much more slowly than in the past several decades, even under the severe-crisis scenario. The stronger price structure is the result of the continuing, gradual slowdown in the rate of growth in both production and consumption. Other structural elements will also hold in place even as changes in welfare occur. The growth in cereal trade remains strong in all three scenarios, and Asia’s role as a major player in cereal and livestock markets in the coming decades is not likely to be threatened by the current crisis. But at the same time the crisis is expected to have its most devastating effect on Asian food security.